PropaNet: Time-Varying Condition-Specific Transcriptional Network Construction by Network Propagation - Ahn, Hongryul; Jo, Kyuri; Jeong, Dabin; Pak, Minwoo; Hur, Jihye; Jung, Woosuk; Kim, Sun (Frontiers in Plant Science, 2019)
Transcription factor (TF) has a significant influence on the state of a cell by regulating multiple down-stream genes. Thus, experimental and computational biologists have made great efforts to construct TF gene networks for regulatory interactions between TFs and their target genes. Now, an important research question is how to utilize TF networks to investigate response of plant stress at the transcription control level using time-series transcriptome data. In this article, we present a new computational network, PropaNet to investigate dynamics of TF networks from time-series transcriptome data using two state-of-the-art network analysis techniques, influence maximization and network propagation. PropaNet uses the influence maximization technique to produce a ranked list of TFs, in the order of TF that explains DEGs better at each time point. Then, a network propagation technique is used to select a group of TFs that explains DEGs best as a whole. For the analysis of Arabidopsis time series data sets from AtGenExpress that were measured under cold and heat stress, we used PlantRegMap as a template TF network and performed PropaNet analysis of the time-series data sets to investigate transcriptional dynamics of Arabidopsis under cold and heat stress. The time varying TF networks showed that Arabidopsis responded to cold and heat stress quite differently. For cold stress, bHLH and bZIP type TFs were first responding TFs and the cold signal influenced histone variants, various genes involved in cell architecture, osmotic and restructuring of cells. However, the consequences of plants under heat stress were up-regulation of genes related to accelerating differentiation and starting re-differentiation. In terms of energy metabolism, the plants under heat stress show elevated metabolic process and resulting in an exhausted status. We believe that PropaNet will be useful for the construction of condition-specific time-varying TF network for time-series data analysis in response to stress. PropaNet will be available at \href{https://bhi-kimlab.github.io/projects/\#PropaNet}{https://bhi-kimlab.github.io/projects/\#PropaNet}.